Maize plants can recover from fall armyworm damage under optimum crop production conditions in humid tropical agro-ecologies - Abang, A.; Nanga, S.N.; Agbodzavu, M.K.; Fotso Kuate, A.; Suh, C.; Masso, C.; Bamba, Z.; Fiaboe, K. (Oxford University Press, 2024)
Farmers in Africa perceive the impact of fall armyworm (FAW) on maize to be significant, but field assessments have shown that yield losses are not significant enough to warrant pesticide interventions. This suggests that relationships between the crop stages, time, and duration of attack can affect the yield. Therefore, assessing the plant’s recovery from damage using individual plants based on defoliation levels could guide whether and when pesticides should be applied. To study this, we selected 120 labeled maize plants corresponding to six levels of FAW defoliation, replicated 20 times, based on an initial damage rating. The rating scale ranged from 1 (no defoliation) to 5 (>75% defoliation) during four planting seasons. Plants with a rating scale of 1 were replicated and treated with a chemical insecticide to keep them undefoliated, and that served as a control. Damage severity was recorded weekly on all plants, starting from emergence until maturity, using the same damage rating scale. Results showed that damage severity varied significantly among different defoliation levels during all seasons. Higher levels of defoliation during dry seasons resulted in significant yield loss only for plants with damage levels 4 and 5, with damage severity ranging from 38.7% to 57.5%. These results indicate that FAW control is unnecessary in the rainy season. In contrast, pesticide interventions should be envisaged in seasons of erratic rainfall, with a significant defoliation threshold level of around 50%, occurring at 8 and 5 wk after planting weeks after planting, respectively for the early and late dry season.